A review on the functional properties of fermented soymilk - KESIKA,Periyanaina (2022)
Abstract Fermented soybean products have been used for several centuries. Fermented soymilk is one of the known soy products with several health benefits. The current literature review recapitulates the various health benefits of fermented soymilk. In vitro and in vivo studies have shown that the consumption of fermented soymilk protects one from cancer, diabetes, hyperlipidemia, etc. It has also been reported that fermented soymilk has immune-modulatory, memory improvement, anti-colitis, and wound healing activities. However, there are few studies to confirm the health benefits of fermented soymilk for human subjects. The dose and duration of the intervention may vary between the animal model and humans. So, additional studies are obligatory to authorize the proposed health benefits of fermented soymilk.